Consolidated, systemic conceptualization, and definition of the "sharing economy". (29th October 2019) - Schlagwein, Daniel; Schoder, Detlef; Spindeldreher, Kai
Abstract: The "sharing economy" has recently emerged as a major global phenomenon in practice and is consequently an important research topic. What, precisely, is meant by this term, "sharing economy"? The literature to date offers many, often incomplete and conflicting definitions. This makes it difficult for researchers to lead a coherent discourse, to compare findings and to select appropriate cases. Alternative terms (e.g., "collaborative consumption, " "gig economy, " and "access economy") are a further complication. To resolve this issue, our article develops a consolidated (based on all prior work) and systemic (relating to the phenomenon in its entire scope) definition of the sharing economy. The definition is based on the detailed analysis of definitions and explanations in 152 sources identified in a systematic literature review. We identify 36 original understandings of the term "sharing economy." Using semantic integration strategies, we consolidate 84 semantic facets in these definitions into 18 characteristics of the sharing economy. Resolving conflicts in the meaning and scope of these characteristics, we arrive at a consolidated, systemic definition. We evaluate the definition's appropriateness and applicability by applying it to cases claimed by the media to be examples of the sharing economy. This article's definition is useful for future research and discourse on the sharing economy.